2017
DOI: 10.1111/jgh.13810
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic meatus scoring scale versus sniff test to predict insertability before transnasal endoscopy: A prospective, randomized study

Abstract: Selection of an optimal meatus insertion tract by an anterior meatuscopy causes lesser nasal pain, epistaxis, and post-procedural side effects in nasal anesthesia and UT-EGD than the conventional sniff test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Official guidelines are not in existence, however, uTNE should be avoided in patients with altered nasal anatomy, severe coagulopathy, and previous nasal trauma or nasal surgery in order to limit epistaxis risk. Other rare complications include mucous discharge, dizziness, headache, earache, eye discharge and sinusitis; however these have been small in number [8,11] and are therefore of limited significance. (Table 1) In 2-6% of cases there is failure of nasal intubation due to narrow nasal passages [12]; in the past we routinely assessed nasal patency pretreatment with a 14/16 French nasal catheter prior to attempting intubation, this, however, is no longer considered necessary, as intubation can be achieved effectively under direct visualization.…”
Section: Performing Transnasal Endoscopy-practicalities and Limitationsmentioning
confidence: 99%
“…Official guidelines are not in existence, however, uTNE should be avoided in patients with altered nasal anatomy, severe coagulopathy, and previous nasal trauma or nasal surgery in order to limit epistaxis risk. Other rare complications include mucous discharge, dizziness, headache, earache, eye discharge and sinusitis; however these have been small in number [8,11] and are therefore of limited significance. (Table 1) In 2-6% of cases there is failure of nasal intubation due to narrow nasal passages [12]; in the past we routinely assessed nasal patency pretreatment with a 14/16 French nasal catheter prior to attempting intubation, this, however, is no longer considered necessary, as intubation can be achieved effectively under direct visualization.…”
Section: Performing Transnasal Endoscopy-practicalities and Limitationsmentioning
confidence: 99%
“…In transnasal endoscopy, nasal pain is the most frequent symptom during insertion 6 14 . Our results revealed that nasal breathing resulted in less nasal pain and discomfort than oral breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the success of transnasal intubation depended on the nasal pretreatment, nasal meatus selection, scope diameter, and endoscopist's skill [2,[14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the TNA condition, a mixture of 1 mL of 2% viscous lidocaine hydrochloride and 1 mL of lubricant was injected up one naris via a syringe. The selected naris of entry was based on the sniff test 40,41 and participant preference. In the placebo condition, 2 mL of lubricant was applied to the same naris.…”
Section: Equipmentmentioning
confidence: 99%